The Effect of Listening Training Program to Vocational High School TOEIC Score Achievement - Zuraida Supri, Ida; Hendar; Heryono, Heri; Lukitawaty Sujatna, Meita (International Journal of Psychosocial Rehabilitation, 2020)
Having adequate English competence is compulsory as one of the fundamental requirements for entering the working world in this global era. All formal levels of education have been providing their students with curriculum that enables them to have good mastery of English. Vocational schools equip their students with English for Specific Purposes so that they can cope with business English in their future jobs. TOEIC is a tool that the vocational schools use to measure the students’ English competence. This research aims at 1) identifying vocational school students’ prior listening English competence 2) analyzing the effects of the listening training program on students’ score achievement in The Listening Part of the TOEIC. The results show that the students prior listening competence is still low. The training program has positive effects to the improvement of students’ achievement of the listening score of the TOEIC test.